2021
DOI: 10.3389/fpubh.2021.769731
|View full text |Cite
|
Sign up to set email alerts
|

Review and Implications of Intergenerational Communication and Social Support in Chronic Disease Care and Participation in Health Research of Low-Income, Minority Older Adults in the United States

Abstract: Background: Health disparities disproportionally affect Black and Hispanic older US adults. Health research is needed to understand and eliminate these disparities; however, older adults, and particularly Black and Hispanic/Latino older adults are underrepresented in health research. Adult children have influenced health behavior and health outcomes of their older parents in several demographics in the US. Analysis of these studies can lead to a model for the development of interventions aimed at improving hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The social support system can improve the self‐management enthusiasm of patients with chronic diseases, and improve their anxiety and depression (Kong et al, 2019; Vaccaro et al, 2021). As one of the main places for social activities, the family is the most important part of the social support system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The social support system can improve the self‐management enthusiasm of patients with chronic diseases, and improve their anxiety and depression (Kong et al, 2019; Vaccaro et al, 2021). As one of the main places for social activities, the family is the most important part of the social support system.…”
Section: Resultsmentioning
confidence: 99%
“…Social support system can not only improve the initiative of chronic disease patients' self‐management, but also improve their negative psychological state (Kong et al, 2019; Vaccaro et al, 2021). Family behaviours can either hinder or promote self‐management (Vongmany et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Ethnically diverse older adults in our study discussed health care issues and decisions regarding research participation with their adult children, especially those in healthcare professions. A recent study, by our group reported evidence that younger adults of several populations have been influential in the lives of older adults and their health care decisions (Vaccaro et al, 2021). However, many older adults in our study stated that they made their decisions independently after consulting their children, especially their daughters.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, research suggests that social support significantly impacts the health outcomes of older adults [ 25 ]. Caregivers can encourage older adults to adopt healthy behaviors and lifestyles to manage their chronic diseases [ 26 ]. Consequently, older adults with robust social support are more inclined to engage in physical activities, maintain a healthy diet, and actively participate in social activities, thereby reducing the incidence and progression of chronic diseases and potentially reducing the occurrence of dysphagia.…”
Section: Discussionmentioning
confidence: 99%